O susto do Bispo Sardinha: algumas possibilidades antropofágicas - Longobardi, Luciana Gama (2010)
This paper proposes a reading of the idea of anthropophagy, developed by Oswald de Andrade in the 20s, having in the central axis two of his major works: A man without profession Under mom s orders and Cannibal Manifesto. For this we used a methodological procedure developed by Guilles Deleuze and Félix Guattari, called by them as rhizome. It is, in the context of this study, a network of connections and steady flows through a discussion of multiplicities whose strength lies in devouring the other. Based on this analytical tool we focus on the narrative style from Oswald de Andrade in which he subverts the model itself, reaching the Brazilian culture under the sign of the mixture and multiplicity